Deporte en tiempo de COVID-19: impacto del confinamiento en la actividad de los equipos - Peña, J.; Altarriba-Bartés, A.; Vicens-Bordas, J.; Gil-Puga, B.; Piniés-Penadés, G.; Alba-Jiménez, C.; Merino-Tantiñà, J.; Baena-Riera, A.; Loscos-Fàbregas, E.; Casals, M. (Apunts Medicina de l'Esport, 2020)
The COVID-19 pandemic has affected many sectors of our global society since its detection in Wuhan in December 2019, and team sports have been no stranger to this reality. This special article presents a review of the literature exposing the dangers for athletes of this virus, reporting the effects of the pandemic on competitive sport, and making evidence-based recommendations to avoid the consequences of detraining in confined athletes. Furthermore, we present the results of a survey with 361 answers computed from coaches and different staff members from 26 different countries, representing the activity of more than 4500 athletes from all over the world. The aim was to know more teams` activity during this cessation period. Finally, the article outlines recommendations based on the answers to help teams if a second outbreak of the virus forces massive confinements again, guiding a safe return to sport at any competitive level.